2012
DOI: 10.1111/j.1365-2125.2012.04301.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrated pharmacokinetics and pharmacodynamics of epoprostenol in healthy subjects

Abstract: Of the two metabolites analyzed, the appearance of 6-keto-prostacyclin F(1α) in plasma was more closely associated with the haemodynamic effects of i.v. epoprostenol. PK and PD profiles showed that CIn relates proportionally and linearly to the plasma concentrations of 6-keto-prostacyclin F(1α) . These results suggest that 6-keto-prostacyclin F(1α) is a suitable surrogate marker of plasma concentrations of epoprostenol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Information regarding the pharmacokinetics/ pharmacodynamics of prostacyclin analogues in patients with advanced CKD is limited and FDA labels do not provide any dosing adjustments [55]. Epoprostenol has a limited half-life of 10 min, and doses are slowly increased over time, making it difficult to study pharmacokinetics because of the rapidity of its clearance [56]. It was previously studied, however, in dialysis patients as an antithrombotic agent at similar doses to the initial dose for pulmonary hypertension [57].…”
Section: Prostacyclin Analogues and Prostacyclin Receptor Antagonistsmentioning
confidence: 99%
“…Information regarding the pharmacokinetics/ pharmacodynamics of prostacyclin analogues in patients with advanced CKD is limited and FDA labels do not provide any dosing adjustments [55]. Epoprostenol has a limited half-life of 10 min, and doses are slowly increased over time, making it difficult to study pharmacokinetics because of the rapidity of its clearance [56]. It was previously studied, however, in dialysis patients as an antithrombotic agent at similar doses to the initial dose for pulmonary hypertension [57].…”
Section: Prostacyclin Analogues and Prostacyclin Receptor Antagonistsmentioning
confidence: 99%
“…Studies have demonstrated that the inactive 6-keto-PGF1a hydrolysis product serves as a stable surrogate measure with a linear dose relationship to intravenously infused epoprostenol. 20,21 However, the blood level of 6-keto-PGF1a attributable to hydrolysis of endogenously produced prostacyclin, or exogenously administered epoprostenol, cannot be differentiated. The metabolite, 6-keto PGF1a, was detected at low levels (average <60 pg/mL) immediately post exposure in the blood of control animals as expected, while a dose-related increase was observed in animals inhaling epoprostenol.…”
Section: Summary/conclusionmentioning
confidence: 99%
“…23 Although clinical studies with the IV administration of epoprostenol AS are limited at present, direct biocompatibility has been shown with respect to pharmacokinetics, pharmacodynamics, safety, and tolerability between epoprostenol GM and epoprostenol AS 24 ; in addition, both products have the same half-life because they contain the same active ingredient. 23 Although clinical studies with the IV administration of epoprostenol AS are limited at present, direct biocompatibility has been shown with respect to pharmacokinetics, pharmacodynamics, safety, and tolerability between epoprostenol GM and epoprostenol AS 24 ; in addition, both products have the same half-life because they contain the same active ingredient.…”
Section: Epoprostenol As (Veletri)mentioning
confidence: 99%